Testing for farmer stock market-unemployment hypothesis during the COVID-19 pandemic in Malaysia - Habibullah, Muzafar Shah; Saari, Mohd Yusof; Lau, Evan; Din, Badariah; Anuar Shah, Bali Mohamad (Inderscience Publishers, 2023)
Farmer hypothesised that there is a linear long-run relationship between the movement of the stock market and movement in the unemployment rate, and there is a unidirectional causality running from stock market to unemployment rate. In this study we test the Farmer hypothesis by using Malaysia’s daily data on stock price and unemployment rate during the COVID-19 pandemic. We performed unit root, cointegration and short-run as well long-run non-causality tests between the stock market and unemployment rate using high frequency data for the period January to October 2020. Our results suggest that both stock market and unemployment rate are non-stationary and cointegrated. The causality test results suggest that using shorter lag, Farmer hypothesis is rejected while at longer lags, Farmer hypothesis cannot be rejected.